STUDY PROGRAM PERFORMANCE IMPROVEMENT MODEL BY WAY OF PERFORMANCE MANAGEMENT SUPPORTED BY UTILIZATION OF INFORMATION TECHNOLOGY AND ORGANIZATIONAL CLIMATE IN UNIKOM - Soegoto, Eddy Soeryanto (Universitas Komputer Indonesia, 2017)
The Performance of Study Program is the determinant factor of Higher Education performance. The decrease of the number of students enrolling in the StudyProgram (Prodi), the accreditation result of Prodi, the duration of student studyand the absorption of alumni are the factors of Prodi performance that have notbeen achieved yet according to the purpose of the Institution. The problem ispointed out that only the utilization of information technology has not beenevenly distributed both to lecturers and employees, to unorganized organizational climate, and performance management that has not been effectively implemented. Based on these phenomena, the purpose of this study is to obtain theresults of the study and analysis of the study program performance model affected by management performance with the help of utilization of informationtechnology and organizational climate.Research approach is quantitative. The object of research is the study programin UNIKOM environment with saturated samples amounted to 27 Study Programs. Data collection uses questionnaires, interviews and documentation. Theanalysis procedure is path analysis.Research result shows that the performance of study program in the UNIKOMenvironment has not been in accordance with institutional expectations, especially in the acquisition of accreditation; Performance management has notbeen effective yet; Utilization of information technology especially software implementation has not been conducive to service to students, and organizationclimate has not been fully support the achievement of Prodi's performance yet,especially in achieving superior accreditation. This research result generates anew model, which is different from the previous research, where the use of information technology, and organizational climate give very low direct effect toProdi's performance, whereas the performance management shows dominanteffect on Prodi's performance. This means that Prodi's performance will be optimal when it has the use of appropriate information technology and organizational climate conducive in supporting effective performance management